THE IMPORTANCE OF CHANGE MANAGEMENT AND LEARNING ORGANIZATIONS TO THE PERFORMANCE OF YOUNG ENTREPRENEURS GROUP OF SERANG CITY: PENTINGNYA MANAJEMEN PERUBAHAN DAN ORGANISASI PEMBELAJARAN TERHADAP KINERJA KELOMPOK PENGUSAHA MUDA KOTA SERANG - Hamdan (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this study was to determine the effect of change management and learning organization on the performance of the Young Entrepreneurs Group in Serang City, especially in the increasingly unpredictable business environment at this time. This research is a quantitative research with data collection techniques through questionnaires. Determination of the sample is done by non-probability sampling with a saturated sampling technique of 71 employees who are members of the Young Entrepreneurs Group. The data analysis technique used is multiple linear regression analysis using the SPSS ver 25.0 application which includes the t test and F test. The results of this study indicate that Change Management has no significant effect on employee performance, the t test results show that t count 0.327 < 1.667 t table with significance level 0.745 > 0.05. Learning Organization has a significant effect on employee performance, the results of the t test show that t count 3.088 > 1.667 t table with a significance level of 0.003 <0.05. The results of the F test show that F count 39.624 > 3.13 F table with a significance level of 0.000 < 0.05, it can be concluded that Change Management and Learning Organizations simultaneously have a positive and significant effect on the Performance of Young Entrepreneurs Group Employees